Omens in Ancient Tamils: பழந்தமிழரின் நிமித்தங்கள் - Karumbayiram (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2021)
It was well-established that the ancient Tamil have observed so-called Internal and external way of life adequately. The literary evidence show that in order to gain the meaning of this Internal and external life, one is meant to leave his partner and live in isolation for some reasons for a considerable time period. Hence, journeys became unavoidable, especially for the sake of the war and materialistic purposes in the classical community. Omens were seen to play significant role among in their life as well, especially when the begun their journey or return home. They serve as significant indications to tip when one shall take the journey or shall not. It is known facts that such practices were still practiced by present-day community. There were a lot of instances showing such situations in the classical literatures, showing the importance of Omen. This article offer descriptions and explanations related to the cause of the omens and its developmental trends. அகமும் புறமும் பண்டைய தமிழரின் வாழ்வியல் நெறியாக விளங்கியது. இந்த அக, புற வாழ்வியலில் பொருள் ஈட்ட வேண்டி, தலைவன் தலைவியை விட்டுப் பிரிய நேர்ந்தது. குறிப்பாகச் சங்கச் சமூகத்தில் போரிடுதல், பொருளீட்டுதல், கற்றல், தூது போன்றவற்றிற்காகப் பிரிதல் என்பது தவிர்க்க முடியாத ஒன்றாக இருந்தது. பிரிந்து செல்பவரின் பயணம் இனிதாக அமையவும் பிரிந்து சென்றவர் திரும்பி வருவதற்குரிய காலத்தைக் கடத்தும்பொழுதும் அவர் எப்பொழுது வருவார் என்பதை அறியவும் நிமித்தங்கள் பார்க்கப்பட்டன. அதன் தொடர்ச்சி இன்றளவும் பலர் தாம் மேற்கொள்ளும் முக்கிய செயலுக்குமுன் நிமித்தம் பார்த்தலை வழக்கமாகக் கொண்டுள்ளனர். அத்தகைய நிமித்தத்தைப் பழந்தமிழர் எதற்கெல்லாம் பார்த்தனர் என்பதை அறிந்து கொள்ள வேண்டியுள்ளது. நிமித்தம் அவர்களுடைய வாழ்க்கைச் சூழலில் எத்தன்மையில் இடம்பெற்றது என்பதைத் தெரிந்து கொள்வதும் அவசியமாகிறது. எனவே, நிமித்தம் தொடர்பான விளக்கங்களையும் அதன் வளர்ச்சிப் போக்குகளையும் எடுத்துக் கூறுவதாய் இக்கட்டுரை அமைந்துள்ளது.